PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL PROBLEM POSING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SMP NEGERI MANDALA - Bergita Balok; Uke Ralmugiz; Agustin Fatmawati; Nur Hasanah Syarief (MEGA: Jurnal Pendidikan Matematika, 2022)
The purpose of this study was to determine the development of a valid, practical and effective Problem Posing Modelas a learning tool. This research and development study (R&D) with 4-D have some phases, namely: define, design, develop, and desiminate. The data collection technique used test (description/essay) and non-test (tool validation and questionnaire). The data were analyzed through validity analysis, practicality analysis, and effectiveness analysis. The instruments used in this study were questionnaires,validation sheets, Lesson Plan, student’s worksheets, and test. The study showed that lesson plan is stated to be very valid with an average score of 90.15 in the k > 80 category andstudent’s worksheets is declared very valid with an average score of 84.58 in the k > 80 category. The students and teachers’ response are stated to be very practical with the average score of 80.55 in the k > 80 category. Besides, the effectiveness is declared effective seen from the students’ learning outcomes with 72% in the 60 ≤ p < 80 category. Thus, it can be concluded that the learning tool developed, Problem Posing Model is declared valid, practical and effective so that it can be used in learning mathematics.